MEMAHAMI WISATA RELIGI DAN SPIRITUAL DARI PERSPEKTIF NILAI HINDU - Astrina, Wayan Ayumita; Suparta, Ida Kade; Suarjaya, I Nyoman Alit (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
The values ​​of the Hindu religion have always been the main basis for its followers in carrying out all their activities. Likewise, in religious and spiritual tourism activities which are termed tīrtha yātrā and have been carried out for a long time and still exist today, of course their actualization is based on these values. This foundation needs to be clearly understood so that it can be maintained or further developed in the tourism sector. Through a study that applies the systematic literature review method, it seeks to clearly describe the understanding of religious and spiritual tourism from a Hindu values ​​perspective. The results of the study show that religious and spiritual tourism naturally has and actualizes principles based on Hindu values. In general, the principles of religious and spiritual tourism reflect the teachings of Tri Hita Kāraṇa, Tri Pramāna, and the Three Frameworks of Hinduism. The relevance of Hindu values ​​can also be applied in the management of religious and spiritual tourism by adopting the principle of